Structure and chromosomal location of the mouse interleukin-12 p35 and p40 subunit genes. - Tone, Y; Thompson, SA; Babik, J; Nolan, K; Tone, M; Raven, C; Waldmann, H (1996)
Interleukin-12 (IL-12) is a heterodimeric cytokine composed of p35 and p40 subunits and is required for induction of T helper 1 (Th1) responses. Knowledge of how the IL-12 gene is regulated will permit an understanding of susceptibility and resistance to pathogenic microbes and to autoiummune diseases. In this report, we provide the gene structures, nucleotide sequences and chromosomal assignment for the p35 and p40 subunits of mouse IL-12. The p35 and p40 subunit genes are distributed over 8 kb and 14 kb, and map to chromosomes 3 and 11, respectively. The p35 subunit gene consists of eight exons, including a 5'-noncoding exon that was defined by sequence comparison of genomic DNA with the 5'ends of novel cDNA molecules. Transcription of p35 mRNA can start from the first exon but can also initiate further downstream. Potential transcription regulatory elements, AP1, AP2, AP3, NF-kB and GATA recognition sequences, are located within 523 bp upstream of the p35 gene; however, no TATA box was identified. The p40 subunit gene consists of eight exons. A TATA box is located 30 bp upstream from the transcription start site, and AP1, AP3, GATA, and Pu.1 recognition sequences are located within 690 bp upstream of the p40 gene. An AGTTTCTACTTT sequence, which acts as an interferon-gamma response element in the promoter of the major histocompatibility complex class I gene, was also found upstream of the p40 gene.